The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.4103/2229-516x.157156
|View full text |Cite
|
Sign up to set email alerts
|

Blood utilization in orthopedic and trauma practice

Abstract: Objectives:Very little is known about blood utilization in orthopedic and trauma surgery and there is no definite policy in this regard. Our objective is to perform an audit on our practice of blood utilization in the orthopedic department.Methods:We have retrospectively analyzed the data of patients who were admitted between January 2011 and December 2012 to the orthopedic male, female and pediatric wards for which blood products were requested.Results:Three hundred and eight patients were admitted for surger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…There are few studies from Saudi Arabia regarding blood bank utilization, and most include small sample sizes and short follow-up periods [2,[7][8][9][10]. A study on blood bank utilization conducted in our center between 1996 and 2000 showed an average C/T ratio of 2.96, which did not meet the international standards of less than 2, and over-ordering of blood products and cancellation of over 60% of transfusions [7,11].…”
Section: Introductionmentioning
confidence: 99%
“…There are few studies from Saudi Arabia regarding blood bank utilization, and most include small sample sizes and short follow-up periods [2,[7][8][9][10]. A study on blood bank utilization conducted in our center between 1996 and 2000 showed an average C/T ratio of 2.96, which did not meet the international standards of less than 2, and over-ordering of blood products and cancellation of over 60% of transfusions [7,11].…”
Section: Introductionmentioning
confidence: 99%